Cursed - Silverstein, Karol Ruth (Watertown, MA : Charlesbridge Teen, 2021)
"Depicts young teen Ricky Blooms struggles with her recent chronic illness diagnosis, which comes amid family upheaval and challenges at school."--Provided by publisher.
"Junior Library Guild Selection"--Back cover of Dust jacket.
Keywords: Rheumatoid arthritis -- Patients; Fiction; People with disabilities -- Fiction; Families -- Fiction; Schools -- Fiction